Retina‐Inspired Organic Photonic Synapses for Selective Detection of SWIR Light. Issue 6 (13th December 2022) - Wang, Song; Chen, Hao; Liu, Tianhua; Wei, Yanan; Yao, Guo; Lin, Qijie; Han, Xiao; Zhang, Chunfeng; Huang, Hui
Abstract: Photonic synapses with the dual function of optical signal detection and information processing can simulate human visual system. However, photonic synapses with selective detection of short‐wavelength infrared (SWIR) light have never been reported, which can not only broaden the human vision region but also integrate neuromorphic computation and infrared optical communication. Here, organic photonic synapses based on a new donor‐acceptor copolymer P1 are fabricated, which exhibit excellent synaptic characteristics with selective detection for SWIR and extremely low energy consumption (2.85 fJ). The working mechanism is rooted in energy level barriers and unbalanced charge transportation. Moreover, these photonic synapses demonstrate excellent performance in multi‐signal logic editing, letter imaging and memory with noise reduction function. This contribution provides ideas of constructing selective‐response synapses for artificial visual system and neuromorphic computing. Abstract : Inspired by the color recognition function of the retina, an artificial photonic synapse, based on a novel narrow‐band gap polymer P1 and PC71 BM, with unprecedentedly selective response to short wavelength infrared (SWIR) light is reported, which realized letter imaging and memory with noise reduction function. This work has the potential to broaden the range of artificial visual systems and facilitate the coupling of neuromorphic computing with optical communication.